Analisis Faktor-Faktor yang Mempengaruhi Minat Belajar Kitab Kuning Pada Remaja di TPQ Al-Ikhlas - Ahsaniyah, Nur; Muzayyin, Muzayyin (IAINU Kebumen, 2025)
This study aims to determine the factors that influence adolescent learning interest and how to find solutions to increase adolescent interest in learning the yellow book at TPQ Al-Ikhlas Kuwayuhan Village. This study uses a qualitative research type with a case study approach. The data needed in this study were collected through observation, interviews and documentation. The data analysis technique used is the Miles and Huberman model data analysis technique, namely data condensation, data presentation and drawing conclusions. Based on the results of the study, it can be concluded that 1) adolescent interest in learning the yellow book at TPQ Al-Ikhlas is influenced by internal factors such as understanding the importance of religious knowledge, learning motivation, the ability to read pegon letters, as well as physical condition and fatigue after school activities, and external factors such as parental support, peer influence, the role of ustadz, and the learning methods used. 2) Solutions that can be done to maintain and increase adolescent interest in learning the yellow book are to foster internal motivation through advice and inspirational stories, provide special training in reading pegon writing with drill and habituation methods, vary learning methods to be more interactive and fun, and link the yellow book material to the context of modern life